Effects of curing modes on depth of cure and microtensile bond strength of bulk fill composites to dentin - Sara N. MAKHDOOM; Karen M. CAMPBELL; Ricardo Marins CARVALHO; Adriana Pigozzo MANSO (University of São Paulo, 2020)
Abstract Objectives To compare the microtensile bond strength (µTBS) and depth of cure (DOC) of bulk-fill composites cured by monowave (MW) and polywave (PW) LED units using different curing times. Methodology Three composites were tested: Tetric EvoCeram Bulk Fill (TBF), Filtek Bulk Fill (FBF), and Tetric EvoCeram (T; control). Flat dentin surfaces treated with adhesive (AdheSE Universal®, Ivoclar Vivadent) were bonded with 4 mm cylindrical samples of each bulk-fill composite material (n=6) and cured with monowave (Satelec) or polywave (Bluephase Style) curing units for 10 or 20 seconds. After 24 hours, teeth were sectioned into individual 0.9 mm2 beams and tested for µTBS. Failure modes were analysed. Moreover, the DOC scrape test (IOS 4090) was completed (n=5) following the same curing protocols. Two-way ANOVA (a=0.05) was performed, isolating light-curing units. Results For samples cured with the MW light-curing unit, no significant effects were observed in the µTBS results between any of the resin composite brands and the curing times. Conversely, when resins were cured with a PW light unit, a significant effect was observed for TBF resin. In general, bulk-fill composites presented greater DOC and longer curing time resulted in higher DOC for all composites. Conclusion The µTBS of the composites to dentin was not affected by the curing mode of the resins, except for TBF cured with PW light unit. Bulk-fill composites exhibit greater DOC than conventional resin-based composites.